2006
DOI: 10.1007/s10800-006-9220-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bubble shape and the thickness of the wetting film on the incremental electrical resistance caused by the presence of a single bubble in Hall-Héroult cells

Abstract: Bubbles play an important role in the transport phenomena existing in an electrolysis cell. They increase the total ohmic resistance of the electrolyte but their contribution is still not well quantified. During their movement under the anode, the bubbles are separated from the solid by the so-called wetting film, that is by a thin liquid layer. In order to develop a mathematical model to compute the increment of the electrical resistance of the electrolyte due to the presence of several bubbles under the anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A strong connection has been found between the specific bubble volume and the cell voltage; a higher bubble volume causes higher cell voltage (Aaberg, 1997). Perron et al (2006d) and Hyde and Welch (1997) have found that the shape of «he bubble does not have much effect on the total electrical resistance but the size does.…”
Section: Fortin Shaped Bubbles In the Cellmentioning
confidence: 99%
“…A strong connection has been found between the specific bubble volume and the cell voltage; a higher bubble volume causes higher cell voltage (Aaberg, 1997). Perron et al (2006d) and Hyde and Welch (1997) have found that the shape of «he bubble does not have much effect on the total electrical resistance but the size does.…”
Section: Fortin Shaped Bubbles In the Cellmentioning
confidence: 99%
“…It is believed that bubble distribution beneath the anode has a large effect on voltage drop as the current mainly flows through the anode-cathode distance [8]. Therefore, if bubbles are also involved in the models, the effects of slotted cathode and heightened collector bar would be hard to define.…”
Section: Analysis Model and Theorymentioning
confidence: 99%